Research priority setting in organ transplantation: a systematic review. (21st February 2017) - Tong, Allison; Sautenet, Benedicte; Chapman, Jeremy R.; Harper, Claudia; MacDonald, Peter; Shackel, Nicholas; Crowe, Sally; Hanson, Camilla; Hill, Sophie; Synnot, Anneliese; Craig, Jonathan C.
Summary: Barriers to access and long‐term complications remain a challenge in transplantation. Further advancements may be achieved through research priority setting with patient engagement to strengthen its relevance. We evaluated research priority setting in solid organ transplantation and described stakeholder priorities. Databases were searched to October 2016. We synthesized the findings descriptively. The 28 studies (n = 2071 participants) addressed kidney [9 (32%)], heart [7 (25%)], liver [3 (11%)], lung [1 (4%)], pancreas [1 (4%)], and nonspecified organ transplantation [7 (25%)] using consensus conferences, expert panel meetings, workshops, surveys, focus groups, interviews, and the Delphi technique. Nine (32%) reported patient involvement. The 336 research priorities addressed the following: organ donation [43 priorities (14 studies)]; waitlisting and allocation [43 (10 studies)]; histocompatibility and immunology [31 (8 studies)]; immunosuppression [21 (10 studies)]; graft‐related complications [38 (13 studies)]; recipient (non‐graft‐related) complications [86 (14 studies)]; reproduction [14 (1 study)], psychosocial and lifestyle [49 (7 studies)]; and disparities in access and outcomes [10 (4 studies)]. The priorities identified were broad but only one‐third of initiatives engaged patients/caregivers, and details of the process were lacking. Setting research priorities in an explicit manner with patient involvement can guide investment toward the shared priorities of patients and health professionals.